FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM MEMUTUSKAN PEMBELIAN ANDROID OLEH MAHASISWA FKIP UNIVERSITAS RIAU - Krisna Dewi; Sakdanur Nas; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : In Indonesia Smartphone with Android Operating System was the most demand. To understand consumer behavior must always be carried out in accordance with the development of information technology. There are many factors that affect consumer behavior in deciding the purchase of android. These factors include cultural factors, social factors, personal factors, psychological factors. The aim of this study was to determine what factors and what are the most dominant factors in influencing consumer behavior in deciding the purchase of android by students FKIP University of Riau by taking 100 students android users. The sampling technique used is the method of sampling non-probability with incidental sampling technique. Collecting data technique used is the questionnaire. While this research data analysis technique used is the analysis of factors. This analysis used analyzing interdependencies between variables. Based on factor analysis conducted, it showed that the KMO test was obtained Sig. 0,000. Because Sign. 0.000 <0.05, it means that there is a correlation between the independent variables. At this stage of the extraction factor gained one factor that has eigenvalue of 2.408 or 60.195%, which shows the influence of cultural factors, personal, social and psychology of consumer behavior, while 39.805% influenced by other factors such as brand mobile phones. Based on the value of the coefficient matrix obtained, the most dominant factor is the personal factor.Key Words: Consumer Behavior; Cultural Behavior, Social, Private and Psychology